Incidence and Possible Risk Factors of Rash Associated with Efavirenz in HIV - infected Patients with Preceding Nevirapine - associated Rash in Chachoengsao Hospital - Tancharoen, Opass (Journal of Health Science of Thailand, 2017)
A retrospective cohort study was done by collecting data from medical records of HIV - in-fected patients diagnosed with nevirapine- associated rash who subsequently received efavirenz inChachoengsao hospital between August 2002 and October 2008. Targeted patients were followedup for at least 3 months after receiving efavirenz. Incidence of secondary drug rash and also riskfactors, including age, gender, baseline CD4 cells count and alanine aminotransferase, previousopportunistic infections and list of concurrent therapeutic drugs caused allergy, severity of nevirapine- associated rash and major concomitant anti-infective drugs, were studied and compared betweenthose who had (experiment) and did not have (control) rash associated with efavirenz. Total of 67patients (56.7% male) were included in the study with a median age of 37 years. Median (and interquartile range) CD4 cell count was 70 (17-209) cells/μL. Of the 67 patients, 5 developed rashassociated with efavirenz (7.46% incidence) and 3 of them required discontinuation of efavirenz.The baseline characteristics of the two groups: experiment (5 patients) and control (62 patients),were similar. None of the risk factors investigated was associated with developing rash associatedwith efavirenz, except for eosinophilia in one case who had widespread rash with systemic symp-tom and also very high eosinophil count, particularly more than 1,500 cells/μL. Median (andinterquartile range) time from nevirapine discontinuation to efavirenz initiation was 10 (8-20) daysin the experiment and 12 (7-20) days in the control (p 0.74). The preceding development of severenevirapine-associated rash had a trend towards a similar rate in both groups (40% vs. 50%; OR 0.67;95% CI 0.10-4.27; p 0.51). The majority (92.54%) of HIV-infected patients with CD4 counts < 250cells/μL in Chachoengsao hospital who had preceding nevirapine-associated rash could tolerateefavirenz well. Efavirenz can be an option for subsequent use in these patients except for precautionin those who had widespread nevirapine-associated rash with systemic symptoms and eosinophilia,especially more than 1500 cells/μL.